2017
DOI: 10.18332/tpc/69850
|View full text |Cite
|
Sign up to set email alerts
|

The Secondhand Smoke Exposure Scale (SHSES): A hair nicotine validated tool for assessing exposure to secondhand smoke among elderly adults in primary care

Abstract: INTRODUCTION Accurate estimation of exposure to Secondhand Smoke (SHS) is important in both research and clinical practice. We aimed to develop, an easy to implement, biomarker validated scale to provide an estimation of adult exposure to SHS for use within primary health care or epidemiological research. METHODS A pool of 26 baseline questions evaluating exposure to SHS was administered to 178 non-smoking adults (mean age 68.1 years), recruited from both urban and rural primary health care practices in Crete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…The development of new models aimed at promoting the quality of life of the elderly population related to tobacco consumption has become a priority today (Vardavas et al, 2017). In this study, the results showed that the elderly who use tobacco and have very low and low levels of nicotine dependence did not present significant differences between the cognitive domains of executive functions compared to the control groups.…”
Section: Discussionmentioning
confidence: 60%
“…The development of new models aimed at promoting the quality of life of the elderly population related to tobacco consumption has become a priority today (Vardavas et al, 2017). In this study, the results showed that the elderly who use tobacco and have very low and low levels of nicotine dependence did not present significant differences between the cognitive domains of executive functions compared to the control groups.…”
Section: Discussionmentioning
confidence: 60%
“…In our opinion the advantage of the scale is that it is easy to use and constitutes a biomarker-validated approach. According to Vardavas et al the correlation between the SHSES and the participants biomarker validated exposure (hair nicotine), indicated a Pearson’s correlation of 0.4939, with a p -value < 0.0001 [ 19 ]. Second of all, we have decided to measure EAT thickness by means of multislice computed tomography.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental tobacco smoke exposure was assessed with SHSES according to Vardavas et al [ 19 ]. SHSES sheet contains four questions, each relating to different site of exposure.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations